Description of two new Pristionchus species from South Korea - Herrmann Matthias; Kanzaki Natsumi; Weiler Christian; Theam Penghieng; Rödelsperger Christian; Sommer Ralf (Journal of Nematology, 2024)
Based on molecular markers, mating experiments, morphological observations and ecological data, two Pristionchus species (Nematoda: Diplogastridae) new to science are described. Both were collected from different Scarabaeoid beetles in South Korea, have a gonochoristic mode of reproduction and fall into a sub-clade of the pacificus clade. Pristionchus coreanus n. sp. does not show a eurystomatous morph under laboratory conditions and might therefore be suitable for the study of gain and loss of polymorphism. Pristionchus hangukensis n. sp. is phylogenetically close to Chinese and Japanese species and helps to separate an Asian clade from an American clade.